Characteristics of the multiple text reading format in the Common Test of University Admission in Japan - Yosuke Mikami; Rie Koizumi (Language Testing in Asia)
Abstract To reflect the new Course of Study, the Japanese Common Test for University Admission, which began in the 2021 academic year, introduced a multiple-text reading format (MTRF) to the English test that did not exist in previous tests. Given that integrating and understanding multiple English texts is a common real-world occurrence, the introduction of MTRF is reasonable. However, there is limited research analyzing the actual state of MTRF in the Common Test for University Admission. This study aimed to fill this gap in the literature. In this study, we analyzed 12 test forms, including trial, main, and makeup tests. The analysis focused on the relationship between the text used and the types of questions asked. The results showed that the MTRF of the Common Test for University Admission has the characteristics of both TOEIC and Cambridge English Qualifications, which are large-scale high-stakes English tests that use the MTRF. In addition, the complexity of the MTRF questions tended to increase over time owing to changes in the Course of Study. This study makes theoretical and pedagogical contributions, for example, by clarifying the skills of examinees and the nature of assessment tasks.